2020
DOI: 10.22435/hsji.v12i2.2239
|View full text |Cite
|
Sign up to set email alerts
|

Profile of malondialdehyde (MDA) and catalase specific activity in plasma of elderly woman

Abstract: AbstrakLatar belakang: Malondialdehida (MDA) merupakan petanda stres oksidatif yang merupakan produk akhir dari reaksi berantai proksidasi lipid. Untuk mencegah stres oksidatif, tubuh mensintesis katalase, suatu enzim antioksidan endogen yang mengkatalisis hidrogen peroksida (H 2 O 2 ) menjadi air dan oksigen. Sampai saat ini kadar MDA dan katalase pada populasi usia lanjut (usila) masih memberikan hasil yang bervariasi dan kadar tersebut pada kelompok usia yang berbeda dalam populasi usila belum pernah dilapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
9
1
1
Order By: Relevance
“…One of the most damaging effects of ROS is lipid peroxidation, and the end product is Malondialdehyde (MDA) (Phaniendra et al, 2015). A high concentration of MDA proves the low antioxidant status so that it cannot prevent the reactivity of free radical compounds and enter the blood vessels (Hardiany et al, 2020). Lipid peroxide can also convert ROS into reactive compounds capable of crosslinking Deoxyribonucleic Acid (DNA) proteins and induce cell apoptosis.…”
Section: Medical Laboratory Technology Journalmentioning
confidence: 99%
“…One of the most damaging effects of ROS is lipid peroxidation, and the end product is Malondialdehyde (MDA) (Phaniendra et al, 2015). A high concentration of MDA proves the low antioxidant status so that it cannot prevent the reactivity of free radical compounds and enter the blood vessels (Hardiany et al, 2020). Lipid peroxide can also convert ROS into reactive compounds capable of crosslinking Deoxyribonucleic Acid (DNA) proteins and induce cell apoptosis.…”
Section: Medical Laboratory Technology Journalmentioning
confidence: 99%
“…Pemeriksaan kadar MDA melalui metode spektofotometer dengan menilai dua molekul asam tiobarbiturat (TBA) berikatan dengan satu molekul MDA menghasilkan komplek TBA-MDA-TBA berwarna merah muda yang mempunyai serapan maksimum pada panjang gelombang 530 nm. Kadar MDA plasma akan dinilai dengan satuan nmol/mL (15,16).…”
Section: Pengumpulan Dan Pengukuran Dataunclassified
“…As research by Clifford et al found that betalain compounds in red beetroot extract can inhibit linoleic damage by cytochrome C oxidase and the oxidation of lipids membrane by metmyoglobin that activated H2O2 and Fe. Furthermore, the study found that betalain in red beetroot extract could inhibit lipid peroxidation due to ROS very effectively (Clifford et al, 2015;Hardiany et al, 2020) The betalain compounds in beetroot extract also function as potent anti-inflammatory agents by an interfering mechanism with pro-inflammatory signaling cascades (Clifford et al, 2015;Martinez et al, 2015;Moreno-Ley et al, 2021). Another important mechanism of the anti-inflammatory effect of red beetroot extract is to weaken the activity of the Nuclear Factor-Kappa B (NF-B) cascade, which is the agent capable of activating and transcribing some of the target genes that regulate and amplify the inflammatory response, such as cytokines, chemokines, cell apoptosis and phagocytic which can cause chronic tissue damage (El Gamal et al, 2014) The purpose of this study was to determine the effect of red beetroot extract in preventing the TNFinflammatory factor and the increasing sunburn of epidermal cells in rats exposed to UVB.…”
Section: Introductionmentioning
confidence: 99%